2020
DOI: 10.1371/journal.pone.0228585
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal bidirectional relations between body dissatisfaction and depressive symptoms among Black adolescents: A cross-lagged panel analysis

Abstract: ObjectiveTo assess the variation in body dissatisfaction and depressive symptoms by weight status and the bi-directional relations between body dissatisfaction and depressive symptoms by weight status among Black adolescents. MethodsA sample of 153 Black adolescents aged 12-13 years, either overweight/obese (n = 57, 37%) or healthy weight (n = 96, 63%), were recruited and evaluated three times over two years (T1, T2 and T3). Measured weight and height were converted to age and sex-specific BMI z-score; body di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 55 publications
(81 reference statements)
4
13
0
7
Order By: Relevance
“…Adolescent girls tend to overestimate their bodies’ size, and boys tend to underestimate it [ 36 ]. Research on the relationship between body dissatisfaction and weight status consistently shows that overweight adolescents, especially obese, report more body dissatisfaction [ 37 , 38 , 39 , 40 ]. However, this relationship seems to be dependent on gender; for instance, underweight girls report the highest levels of body satisfaction [ 38 ], whereas underweight boys show body dissatisfaction [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescent girls tend to overestimate their bodies’ size, and boys tend to underestimate it [ 36 ]. Research on the relationship between body dissatisfaction and weight status consistently shows that overweight adolescents, especially obese, report more body dissatisfaction [ 37 , 38 , 39 , 40 ]. However, this relationship seems to be dependent on gender; for instance, underweight girls report the highest levels of body satisfaction [ 38 ], whereas underweight boys show body dissatisfaction [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to body dissatisfaction, weight status has not been consistently related to depressive symptoms. Some studies reported that overweight and obese individuals report higher levels of depression [ 45 , 46 ] and that underweight girls present high levels of depression [ 45 ], whereas others showed no differences in depression levels for different weight status [ 19 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outro estudo realizado com adolescentes negros também encontrou prevalência de sintomas depressivos mais elevadas em mulheres (média de 6,00 vs. 2,31, p = 0,080), porém não houve diferenças na insatisfação corporal por sexo (Wang, 2020).…”
Section: Discussionunclassified
“…Um estudo encontrou evidências de que adolescentes negros são menos vulneráveis às pressões relacionadas ao ideal de magreza, em comparação com adolescentes brancos. Além disso, mais de três quartos das mães dos adolescentes negros de baixa renda avaliados nesse estudo estavam ou com sobrepeso ou obesas, podendo indicar que adolescentes negros de baixa renda então protegidos do ideal de magreza (Wang, 2020).…”
Section: Discussionunclassified